PERSEPSI SISWA KELAS III MADRASAH IBTIDAIYAH TPI TERHADAP EFEKTIVITAS PENGGUNAAN VIDEO PEMBELAJARAN PADA MATA PELAJARAN FIKIH:STUDI FENOMENOLOGI - Farid Wajdi (PT. Hasba Edukasi Mandiri, 2026)
Digital transformation in education has driven the integration of multimedia technology into Islamic schooling, including in Fiqh subjects which ontologically demand procedural understanding and practical implementation. Conventional teaching methods, which tend to be abstract, often trigger cognitive overload for Islamic elementary school (Madrasah Ibtidaiyah) students who are still in the concrete operational stage of development. This study aims to deeply explore and analyze the subjective perceptions and lived experiences of third-grade students at MI TPI regarding the effectiveness of using instructional videos in Fiqh lessons. Employing a qualitative approach with a phenomenological research design , data were gathered from the conscious experiences of student informants through in-depth interviews. The findings reveal four main themes: (1) visual representations in videos serve as cognitive scaffolding that deconstructs abstract Fiqh material into concrete forms; (2) videos act as affective catalysts that increase attention and motivation, despite an ambivalence regarding the potential seductive details effect; (3) variations in individual student perceptions are influenced by their respective Zone of Proximal Development (ZPD) and working memory capacities ; and (4) excessive frequency of video use potentially triggers habituation and media saturation, which diminishes its instructional value. This study concludes that instructional videos function optimally as scaffolding rather than as a substitute for the teacher's role. The implications of this study emphasize the importance of teachers possessing Technological Pedagogical Content Knowledge (TPACK) to orchestrate digital media in a balanced manner.